Implementation of a low-cost agricultural machine for the soft dry corn harvesting process originating in the Andean region - Tapia, Melton; Arla, Sandra; Tapia, Edison (Enfoque UTE, 2017)
An agricultural machine of compact size, low cost of manufacture and operation, has been developed for the process of threshing the soft dry corn, originating from the Ecuadorian Andean Region. The simple manufacturing prototype is unique for application in the aforementioned corn species. The main contribution of this development is to provide the farmer with a simple tool that allows him to technify the operation of corn harvesting, an operation that is critical in the harvest stage.